2014
DOI: 10.1109/tcst.2013.2293627
|View full text |Cite
|
Sign up to set email alerts
|

Mode-Independent <inline-formula> <tex-math notation="LaTeX">${\cal H}_{2}$ </tex-math> </inline-formula>-Control of a DC Motor Modeled as a Markov Jump Linear System

Abstract: The paper presents a control strategy for Markov jump linear systems (MJLS) with no access to the Markov state (or mode). The controller is assumed to be in the linear state-feedback format and the aim of the control problem is to design a static mode-independent gain that minimizes a bound to the corresponding H 2 -cost. This approach has a practical appeal since it is often difficult to measure or to estimate the actual operating mode. The proposed result is compared with a previous design, and its usefulnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Now, we give the objective of this work: propose a security SMC scheme for attaining the SFTB for MJS (5) in the face of channel fading (1) and deception attacks (2).…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, we give the objective of this work: propose a security SMC scheme for attaining the SFTB for MJS (5) in the face of channel fading (1) and deception attacks (2).…”
Section: System Descriptionmentioning
confidence: 99%
“…As a special class of stochastic switching systems, Markovian jump systems (MJSs) present a powerful modeling ability for many practical plants that may be disrupted by unpredictable structural changes. [1][2][3] Hence, in the past decades, a wonderful of interesting results have been published on the analysis and synthesis of MJSs in References 4-6 and the reference therein. As one can easily note that the aforementioned works were mainly interested in the infinite-time behavior of dynamic systems, that is, the asymptotic stability as time tends to infinite.…”
Section: Introductionmentioning
confidence: 99%
“…The DC motor device is given to demonstrate the validity and practicability of our design technique. The DC motor device [46] can be modeled as system…”
Section: A Practical Examplementioning
confidence: 99%
“…[1][2][3][4][5] As a consequence, MJSs have wide applications in some real areas such as networked control systems, power systems, economic systems, biological systems, robotic manipulators and so on. [6][7][8] Up to now, lots of research works on MJSs have been reported, such as stability analysis, 9,10 the controller/filter design. [10][11][12] However, the majority of previous results showed that the designed controller/filter were synchronized with the system state.…”
Section: Introductionmentioning
confidence: 99%
“…As a special hybrid system, Markov jump systems (MJSs) received a great deal of attention in the past decades because of their remarkable ability to describe the abrupt failures or environmental changes in practical systems 1‐5 . As a consequence, MJSs have wide applications in some real areas such as networked control systems, power systems, economic systems, biological systems, robotic manipulators and so on 6‐8 . Up to now, lots of research works on MJSs have been reported, such as stability analysis, 9,10 the controller/filter design 10‐12 .…”
Section: Introductionmentioning
confidence: 99%